Addressing the environmental sustainability of plastics used in agriculture: a multi-actor perspective - Valentina E. Tartiu; Rachel Hurley; Cecilie Baann; Demetres Briassoulis; Evelia Schettini; Fabiana Convertino; Bernard Le Moine; Adalgisa Martinelli; Luc Vernet; Sissel B. Ranneklev; Violette Geissen; Esperanza Huerta Lwanga; et al. (Cambridge Prisms: Plastics)
Plastics used in agriculture, commonly known as agriplastics (AP), offer numerous advantages in terrestrial agriculture, forestry, fisheries and aquaculture, but the diffusion of AP-intensive practices has led to extensive pollution. This review aims to synthesise scientific and policy discussions surrounding AP, examining evidence of their benefits and detrimental environmental and agricultural impacts. Following the proposal of a preliminary general taxonomy of AP, this paper presents the findings from a survey conducted among international experts from the plastic industry, farmer organisations, NGOs and environmental research institutes. This analysis highlights knowledge gaps, demands and perspectives for the sustainable future use of AP. Stakeholder positions vary on the options of ‘rejection’ or ‘reduction’ of AP, as well as the role of alternative materials such as (bio)degradable and compostable plastics. However, there is consensus on critical issues such as redesign, labelling, traceability, environmental safety standards, deployment and retrieval standards, as well as innovative waste management approaches. All stakeholders express concern for the environment. A ‘best practice’-based circular model was elaborated capturing these perspectives. In the context of global food systems increasingly reliant on AP, scientists emphasise the need to simultaneously preserve nature-based and traditional knowledge-based sustainable agricultural practices to enhance food system resilience.